DETERMINAN KINERJA KEUANGAN PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) - Pratama, Arif Yuda Nur; Kadarningsih, Ana (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
This study aims to determine the impact of financial ratios on financial performance of companies listed on JII for the 2016-2020 period. The financial ratios used in this study include Liquidity Ratios proxied by Current Ratio (CR), Leverage Ratios proxied by Debt to Equity Ratio (DER), Activity Ratios proxied by Total Asset Turnover (TATO), and Financial Performance as proxied by Return On Assets (ROA). This research is a type of quantitative research. The type of data used in this research is secondary data. The source of the data obtained in the study comes from financial reports that can be accessed through www.idx.co.id and the company`s official website. The population used in this study are companies registered with JII totally 43 companies. The sample used is 25 companies with purposive sampling method. The analytical method used is descriptive statistical test, correlation analysis, classical assumption test, multiple linear regression test, determination test and T test using the SPSS version 24 test tool. The results of the study can be partially formulated that the Current Ratio (CR) variable has no effect to Return On Assets (ROA). Meanwhile, Debt to Equity Ratio (DER) have negative significantly effect and Total Asset Turnover (TATO) have a significant positive effect on Return On Assets (ROA).